STUDI PERUBAHAN MORFOLOGI SUNGAI SERAYU HILIR AKIBAT DEBIT BANJIR - Novi Andhi Setyo Purwono; Ary Sismiani (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2018)
The Serayu River Basin (DAS) is one of the watersheds in Serayu Bogowonto River, the problems that occur in the river channel is the degradation and erosion of river cliffs in recent years. Degradation anderosion of the cliffs resulted in sediment movement within the river channel so that attention needs to betaken to control the destructive power of water in the land around the river and in the river channel.Alluvial river stability is said to be in stable condition or to achieve balance if there are temporary or nonpermanent changes in the medium term.Result of simulation of hydrodynamic behavior of serayu river with constant flood discharge when repeated10 years some locations have erosion and some locations have deposition. The rate of erosion andsedimentation for each Bench Mark is different depending on the position on the outer corner, inner bend,or on a straight groove. Given the phenomenon of some areas that are in the rivers serayu erosion. It isnecessary to immediately do the handling by making a cliff reinforcement or by making a crib to direct thecurrent to the middle so as not to erode the right and left bank of the riverKeywords : river morphology, serayu river, numerical analysi